2019
DOI: 10.1007/jhep08(2019)134
|View full text |Cite
|
Sign up to set email alerts
|

Neutrino masses and mixing from double covering of finite modular groups

Abstract: We extend the even weight modular forms of modular invariant approach to general integral weight modular forms. We find that the modular forms of integral weights and level N can be arranged into irreducible representations of the homogeneous finite modular group Γ N which is the double covering of Γ N . The lowest weight 1 modular forms of level 3 are constructed in terms of Dedekind eta-function, and they transform as a doublet of Γ 3 ∼ = T . The modular forms of weights 2, 3, 4, 5 and 6 are presented.We bui… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
152
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 152 publications
(167 citation statements)
references
References 60 publications
0
152
0
Order By: Relevance
“…(11) that the linear space M k (Γ(4)) has dimension 2k + 1. As shown in [12,32], the even weight modular forms of level 4 can be decomposed into irreducible representations of the inhomogeneous finite modular groups Γ 4 ∼ = S 4 , while odd weight modular forms can be arranged into irreducible representations of the homogeneous finite modular groups Γ 4 which is the double covering group of S 4 . In the present work, we shall focus on the modular forms of even weights.…”
Section: Modular Forms Of Levelmentioning
confidence: 99%
See 2 more Smart Citations
“…(11) that the linear space M k (Γ(4)) has dimension 2k + 1. As shown in [12,32], the even weight modular forms of level 4 can be decomposed into irreducible representations of the inhomogeneous finite modular groups Γ 4 ∼ = S 4 , while odd weight modular forms can be arranged into irreducible representations of the homogeneous finite modular groups Γ 4 which is the double covering group of S 4 . In the present work, we shall focus on the modular forms of even weights.…”
Section: Modular Forms Of Levelmentioning
confidence: 99%
“…It is remarkable that even the A 4 modular models can reproduce the measured neutrino masses and mixing angles [12,19,23]. The modular invariance approach has been extended to include odd weight modular forms which can be decomposed into irreducible representations of the the homogeneous finite modular group Γ N [32], and the modular symmetry Γ 3 ∼ = T has been discussed. It has been shown that the modular symmetry can be consistently combined with generalized CP symmetry, and the modulus τ transforms as τ → −τ * under the CP transformation [33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The generalized CP symmetry in modular invariant models are studied in [42]. The formalism of modular invariant approach has extended to include odd weight modular forms [43].…”
Section: Introductionmentioning
confidence: 99%
“…The modular forms of weight k and level N span a linear space M k (Γ(N )) with finite dimension. As has been shown in [25,43], we can choose the basis vectors of M k (Γ(N )) such that they can be organized into multiplets of modular forms F r (τ ) ≡ (f 1 (τ ), f 2 (τ ), . .…”
Section: Introductionmentioning
confidence: 99%